2023
DOI: 10.1186/s13722-023-00382-1
|View full text |Cite
|
Sign up to set email alerts
|

Treating opioid use disorder in veterans with co-occurring substance use: a qualitative study with buprenorphine providers in primary care, mental health, and pain settings

Abstract: Background Most people with opioid use disorder (OUD) have co-occurring substance use, which is associated with lower receipt of OUD medications (MOUD). Expanding MOUD provision and care linkage outside of substance use disorder (SUD) specialty settings is a key strategy to increase access. Therefore, it is important to understand how MOUD providers in these settings approach care for patients with co-occurring substance use. This qualitative study of Veterans Health Administration (VA) clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…33,39,40 Previous research has identified both stigma and a lack of provider knowledge of clinical guidelines as reasons patients experience opioid withdrawal in healthcare settings. 23,28 Our study advances these findings by highlighting the difficulty some hospital providers had differentiating specific withdrawal symptoms, which could delay appropriate opioid withdrawal treatment. Taken together, these findings are worrisome, as stigma and untreated withdrawal are likely causes of patient-directed discharge.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…33,39,40 Previous research has identified both stigma and a lack of provider knowledge of clinical guidelines as reasons patients experience opioid withdrawal in healthcare settings. 23,28 Our study advances these findings by highlighting the difficulty some hospital providers had differentiating specific withdrawal symptoms, which could delay appropriate opioid withdrawal treatment. Taken together, these findings are worrisome, as stigma and untreated withdrawal are likely causes of patient-directed discharge.…”
Section: Discussionmentioning
confidence: 66%
“…A recent qualitative study of Veterans Affairs primary care providers' experiences and perspectives treating patients with multiple SUDs identified barriers at the patient (e.g., life instability, stigma), provider (e.g., lack of knowledge or clear guidelines), and system levels (e.g., low accessibility to specialty SUD clinics providing MOUD). 23 However, patient presentations and healthcare delivery in the hospital may be substantially different than outpatient settings. Therefore, a deeper understanding of hospital providers' experiences and perspectives is needed to inform the development and implementation of targeted services for hospitalized patients with co-use.…”
Section: Providers' Experiences and Perspectives In Treating Patients...mentioning
confidence: 99%
See 1 more Smart Citation